Enrichment of enzymatically mineralized gellan gum hydrogels with phlorotannin-rich Ecklonia cava extract Seanol® to endow antibacterial properties and promote mineralization. (10th August 2016) - Douglas, Timothy E L; Dokupil, Agnieszka; Reczyńska, Katarzyna; Brackman, Gilles; Krok-Borkowicz, Malgorzata; Keppler, Julia K; Božič, Mojca; Van Der Voort, Pascal; Pietryga, Krzysztof; Samal, Sangram Keshari; Balcaen, Lieve; van den Bulcke, Jan; et al.
Abstract: Hydrogels offer several advantages as biomaterials for bone regeneration, including ease of incorporation of soluble substances such as mineralization-promoting enzymes and antibacterial agents. Mineralization with calcium phosphate (CaP) increases bioactivity, while antibacterial activity reduces the risk of infection. Here, gellan gum (GG) hydrogels were enriched with alkaline phosphatase (ALP) and/or Seanol ®, a seaweed extract rich in phlorotannins (brown algae-derived polyphenols), to induce mineralization with CaP and increase antibacterial activity, respectively. The sample groups were unmineralized hydrogels, denoted as GG, GG/ALP, GG/Seanol and GG/Seanol/ALP, and hydrogels incubated in mineralization medium (0.1 M calcium glycerophosphate), denoted as GG/ALP_min, GG/Seanol_min and GG/Seanol/ALP_min. Seanol ® enhanced mineralization with CaP and also increased compressive modulus. Seanol ® and ALP interacted in a non-covalent manner. Release of Seanol ® occurred in a burst phase and was impeded by ALP-mediated mineralization. Groups GG/Seanol and GG/ALP/Seanol exhibited antibacterial activity against methicillin-resistant Staphylococcus aureus . GG/Seanol/ALP_min, but not GG/Seanol_min, retained some antibacterial activity. Eluates taken from groups GG/ALP_min, GG/Seanol_min and GG/ALP/Seanol_min displayed comparable cytotoxicity towards MG-63 osteoblast-like cells. These results suggest that enrichment of hydrogel biomaterials with phlorotannin-rich extracts is a promising strategy to increase mineralizability and antibacterial activity.